Strategies That Reduce 90‐Day Readmissions and Inpatient Costs After Liver Transplantation. Issue 11 (8th November 2018) - Zeidan, Joseph H.; Levi, David M.; Pierce, Ruth; Russo, Mark W.
Abstract : Liver transplantation (LT) is hospital‐resource intensive and associated with high rates of readmission. We have previously shown a reduction in 30‐day readmission rates by implementing a specifically designed protocol to increase access to outpatient care. The aim of this work is to determine if the strategies that reduce 30‐day readmission after LT were effective in also reducing 90‐day readmission rates and costs. A protocol was developed to reduce inpatient readmissions after LT that expanded outpatient services and provided alternatives to readmission. The 90‐day readmission rates and costs were compared before and after implementing strategies outlined in the protocol. Multivariable analysis was used to control for potential confounding factors. Over the study period, 304 adult primary LTs were performed on patients with a median biological Model for End‐Stage Liver Disease of 22. There were 112 (37%) patients who were readmitted within 90 days of transplant. The readmission rates before and after implementation of the protocol were 53% and 26%, respectively ( P < 0.001). The most common reason for readmission was elevated liver tests/rejection (24%). In multivariable analysis, the protocol remained associated with avoiding readmission (odds ratio, 0.33; 95% confidence interval, 0.20‐0.55; P < 0.001). The median length of stay after transplant before and after protocol implementation was 8 days and 7 days, respectively. A greater proportion of patients were discharged to hospital lodging after protocol implementation (10% versus 19%; P = 0.03). The 90‐day readmission costs were reduced by 55%, but the total 90‐day costs were reduced by only 2.7% because of higher outpatient costs and index admission costs. In conclusion, 90‐day readmission rates and readmission costs can be reduced by improving access to outpatient services and hospital‐local lodging. Total 90‐day costs were similar between the 2 groups because of higher outpatient costs after the protocol was introduced.